Effect of Long-term Administration of Ferula Gummosa Root Extract on Serum Oxidant-antioxidant Status: Effect of long-term administration of Ferula gummosa root extract on serum oxidant-antioxidant status - Ahmad Ghorbani,; Marzieh Mogharrabi,; Reza Mohebbati,; Seyed Mojtaba Mousavi,; Shima Hasan zadeh,; Marzieh Emamian,; Atieh Baharloo,; Mohammad Soukhtanloo, (Iranian Journal of Pharmaceutical Sciences, 2016)
Ferula gummosa Boiss is a good source of biologically active compounds such as monoterpene and sesquiterpene derivatives. There are also several reports on antioxidant effects of these compounds. The aim of this study was to investigate the effect of daily administration of F. gummosa root hydro-alcoholic extract on serum oxidant-antioxidant status. Twenty four Wistar rats were randomly divided into three groups: (1) control, (2) F. gummosa extract 100 mg/kg, and (3) F. gummosa extract 600 mg/kg. The extract was administered by orogastric gavage once daily for 28 consecutive days. The activity of catalase and superoxide dismutase (SOD) enzymes, and the level of malondialdehyde (MDA, as a marker of lipid peroxidation) and total thiol groups were evaluated in blood samples of fasting animals on day 0 and day 28. F. gummosa extract at both doses significantly increased the activity of catalase (p<0.01). The extract at dose of 600 mg/kg significantly increased the activity of SOD (p<0.05), and reduced the level of MDA. F. gummosa had no effect on content of total thiol groups. In conclusion, long-term consumption of hydro-alcoholic extract of F. gummosa root increases the defense of the body against oxidative stress by increasing the activity of catalase and SOD, and by reducing lipid peroxidation.